2016
DOI: 10.1001/jamasurg.2016.1248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cervical Spine Clearance by Computed Tomographic Scan Alone in Intoxicated Patients With Blunt Trauma

Abstract: In this study, alcohol or drug intoxication was common and resulted in significant delays to cervical spine clearance. Computed tomographic scans were highly reliable for identifying all clinically significant CSIs. Spine clearance based on a normal CT scan among intoxicated patients with no gross motor deficits appears to be safe and avoids prolonged and unnecessary immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Other studies have investigated the utility of CT scan to allow clearance of the C-spine in obtunded non-intubated patients presenting to the Emergency Department (14,15). To the best of our knowledge this is the rst study in the literature to focus on the feasibility of CT scan-based cervical spine clearance in intubated trauma victims admitted to a Trauma Intensive Care Unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have investigated the utility of CT scan to allow clearance of the C-spine in obtunded non-intubated patients presenting to the Emergency Department (14,15). To the best of our knowledge this is the rst study in the literature to focus on the feasibility of CT scan-based cervical spine clearance in intubated trauma victims admitted to a Trauma Intensive Care Unit.…”
Section: Discussionmentioning
confidence: 99%
“…Two seminal articles published in 2016 and 2017 strongly supported the use of CT scan alone to exclude signi cant cervical spine injury in emergency department (ED) patients who failed NEXUS criteria; a prospective group of over 1600 alcohol-intoxicated patients, and a retrospective study of over 10 000 patients (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Using a single institution's data, this study showed that a normal CT finding alone could predict the absence of significant spinal injuries in more than 99% of cases. 3 The results of this study suggest that it is unnecessary to delay cervical spine clearance until intoxicated patients are sober or until magnetic resonance imaging is performed. However, caution must be taken in making conclusions based on these data.…”
mentioning
confidence: 86%
“…With the higher potential for this nature of error in lower-resourced settings, it becomes important to compare the costs and benefits of early removal of cervical collars. Bush et al 3 showed that the average cervical spine clearance times were 6 to 12 hours longer among intoxicated patients compared with sober patients, presumably equivalent to the time required to become sober. The increased risk of pressure ulcers, which is the most commonly reported adverse effect associated with prolonged collar use, has been demonstrated only in patients who remain in cervical collars for more than 24 hours.…”
mentioning
confidence: 99%
See 1 more Smart Citation